SOCIO-ECONOMIC IMPACTS OF SELECTED PROCESSING METHODS AMONG ARTISANAL FISH PROCESSORS AROUND RIVER GBAKO, NIGER STATE, NIGERIA - YISA, T.A.; OYERO, J. O.; NDANITSA, M.A. (Nigerian Journal of Fisheries, 2012)
The study was carried out to look at the socio-economic implications of the use of solar tent dryers and smoking/sun-drying methods among the artisanal fish processors around river Gbako, Niger State, Nigeria. The study examined the socio-economic characteristics of artisanal fish processors in the area, being a major tributary from River Niger. Structured questionnaire was designed to elicit information from forty (40) respondents that were randomly selected. Analytical tools used were descriptive statistics such as percentages, profitability analysis and regression. The results showed that 87.5 % of females were involved in fish processing. The profitability analysis indicated that 27.5 % of the fish processors make profit of between ₦1,001 and ₦1,500. The regression results showed that the variables were significant at 1% and 5 % levels. Although, 75 % of the fish processors adopt smoking method as a practice to process fish, their living standard and socio-economic wellbeing could be better if other processing methods such as solar tent dryers are incorporated. It is therefore recommended that Government and non-governmental organizations should review the policy of input subsidization and production credit to smallscale fishers to boost their fish business.